Extinction Training Regulates Neuroadaptive Responses to Withdrawal from Chronic Cocaine Self-Administration - Self, David W. (Cold Spring Harbor Laboratory Press, 2004)
Cocaine produces multiple neuroadaptations with chronic repeated use. Many of these neuroadaptations can be reversed or normalized by extinction training during withdrawal from chronic cocaine self-administration in rats. This article reviews our past and present studies on extinction-induced modulation of the neuroadaptive response to chronic cocaine in the mesolimbic dopamine system, and the role of this modulation in addictive behavior in rats. Extinction training normalizes tyrosine hydroxylase levels in the nucleus accumbens (NAc) shell, an effect that could help ameliorate dysphoria and depression associated with withdrawal from chronic cocaine use. Extinction training also increases levels of GluR1 and GluR2/3 AMPA receptor subunits, while normalizing deficits in NR1 NMDA receptor subunits, in a manner consistent with long-term potentiation of excitatory synapses in the NAc shell. Our results suggest that extinction-induced increases in AMPA and NMDA receptors may restore deficits in cortico-accumbal neurotransmission in the NAc shell and facilitate inhibitory control over cocaine-seeking behavior. Other changes identified by gene expression profiling, including up-regulation in the AMPA receptor aggregating protein Narp, suggest that extinction training induces extensive synaptic reorganization. These studies highlight potential benefits for extinction training procedures in the treatment of drug addiction.